(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. La crisi della Respublica Christiana e la nascita della Chiesa territoriale di Stato - 2. La politica ecclesiastica della Church of England - 3. Dal Toleration Act del 1689 al sincretismo religioso anglicano - 4. Sinodalità anglicana e corresponsabilità nel governo ecclesiale - 5. Osservazioni conclusive. The discipline of the religious factor in the Church of England: perspectives on constitutional inclusivism ABSTRACT: The Church of England reproduced the characteristics of national churches in which rulers were free to choose the religion to be professed and subjects obliged to observe it. This condition persisted until 1689 when William III of Orange passed an ʹact of tolerationʹ by which a certain religious freedom was fostered, albeit in embryonic form, effectively paving the way for the stabilization of the different sensibilities, theological and ecclesiological, present in the aforementioned ecclesial reality and currently converged in the High Church, Low Church and Broad Church. In this regard, it is worth recalling the positive factors that these components have offered to today’s Anglican Church, among which the right of ecclesial reorganization, inclusivism and lay participation in ecclesiastical government undoubtedly stand out. In the latter direction, therefore, must be understood the Synodical Government Measure of 1969 by which a parallel constitutional structure, inspired by the revaluation of the synodal element, through which the ʹequalʹ participation of bishops, presbyters and laity in the potestas gubernandi was ensured in the Church of England, alongside the secular hierarchical chain that reaches from the sovereign down to the faithful, was introduced. Indeed, it is no accident that the Anglican Church "is episcopally led and synodically governed”.